Intellectual Property and the WTO - Fink, Carsten (World Bank, Washington, DC, 2017)
One of the most significant developments of the Uruguay Round of Trade Negotiations (1986-94) was the inclusion of intellectual property rights (IPRs) issues on the agenda of the multilateral trading system. The resulting Agreement on Trade-Related Intellectual Property Rights (TRIPS) is one of three pillar agreements, setting out the legal framework in which the World Trade Organization (WTO) has operated since the end of the Uruguay Round. For the multilateral trading system, TRIPS marked the departure from narrow negotiations on border measures such as tariffs and quotas toward the establishment of multilateral rules for trade-affecting measures beyond borders. This move reflected underlying trends in international commerce. Due to the growth of trade in knowledge and information-intensive goods, the economic implications of imitation, copying, and counterfeiting had in many industries become at least as relevant for international commerce as conventional border restrictions to trade. Yet the TRIPS negotiations on intellectual property were marked by significant North-South differences. Developed countries, which host the world’s largest intellectual property-producing industries, were the key advocates for comprehensive minimum standards of protection and enforcement of IPRs. By contrast, many developing countries, which see themselves mostly as a consumer of intellectual property, felt that stronger standards of protection would serve to limit access to new technologies and products, thereby undermining poor countries’ development prospects. Not surprisingly, the TRIPS Agreement remains one of the most controversial agreements of the WTO.This short paper seeks to provide an introduction to the main instruments used to protect intellectual property in section second, the key economic trade-offs of stronger IPRs in section third, the basic provisions of the TRIPS Agreement in section four, and recent TRIPS developments affecting access to medicines in developing countries in section five.